2020
DOI: 10.1126/scitranslmed.aav0820
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 inhibitors induce reversible changes in nonhuman primate lungs without measurable pulmonary deficits

Abstract: The kinase-activating mutation G2019S in leucine-rich repeat kinase 2 (LRRK2) is one of the most common genetic causes of Parkinson’s disease (PD) and has spurred development of LRRK2 inhibitors. Preclinical studies have raised concerns about the safety of LRRK2 inhibitors due to histopathological changes in the lungs of nonhuman primates treated with two of these compounds. Here, we investigated whether these lung effects represented on-target pharmacology and whether they were reversible after drug withdrawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 29 publications
9
102
2
Order By: Relevance
“…Rab12 phosphorylation was signi cantly lower than wildtype levels in lung. It is possible that lung tissue is more sensitive to LRRK2 inhibition than other tissues considered here and has also been suggested in a recent study investigating the toxicological and morphological effects of LRRK2 inhibition on nonhuman primate lungs, in which high doses of three structurally distinct LRRK2-speci c inhibitors, including MLi-2, induced vacuolated cytoplasm in type II pneumocytes, however no pulmonary de cits were observed (16). These data suggest that there is a lung-speci c LRRK2-dependent mechanism that is affected by chronic LRRK2 inhibition.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Rab12 phosphorylation was signi cantly lower than wildtype levels in lung. It is possible that lung tissue is more sensitive to LRRK2 inhibition than other tissues considered here and has also been suggested in a recent study investigating the toxicological and morphological effects of LRRK2 inhibition on nonhuman primate lungs, in which high doses of three structurally distinct LRRK2-speci c inhibitors, including MLi-2, induced vacuolated cytoplasm in type II pneumocytes, however no pulmonary de cits were observed (16). These data suggest that there is a lung-speci c LRRK2-dependent mechanism that is affected by chronic LRRK2 inhibition.…”
Section: Discussionmentioning
confidence: 71%
“…However, as LRRK2 is expressed endogenously in many tissues and kinase inhibition is predicted to affect both mutant and wild-type LRRK2, whether such inhibitors would be safe to use clinically is uncertain. Preclinical studies have reported macroscopic changes in vivo that include morphological changes in lung from nonhuman primates, and kidney tissue from rats treated with speci c LRRK2 inhibitors that are reversible after termination of treatment (14)(15)(16). Importantly, some of these effects overlap with those seen in Lrrk2 knockout mice (17) demonstrating that they result from ontarget effects of inhibitors on LRRK2 itself rather than resulting from inhibition of other kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Results of the collaborative study showed that the changes seen in lung were indeed due to an apparent direct action on LRRK2. However, these changes were completely reversible after a two-week washout of drug and the group found no lung functional consequences despite the high drug exposures achieved [37]. In a separate MJFF-supported effort, investigators reported that people who carry heterozygous loss-of-function LRRK2 variants, leading to reduced LRRK2 protein levels, do not have reduced life expectancy, nor show more specific disease-related phenotypes [38].…”
Section: Foster Translation Of Lrrk2 Into Therapiesmentioning
confidence: 99%
“…Altogether this evidence may call for a therapeutic strategy targeting LRRK2 kinase activity. Several brain penetrant LRRK2 selective inhibitors have been identified [reviewed in (Ding e Ren 2020)]; however the broad expression of LRRK2 in other organs apart from the central nervous system, including lung, kidney and the immune system raise issues about side effects (Baptista et al 2013;Fuji et al 2015;Herzig et al 2011b;Ness et al 2013;Tong et al 2010b;Baptista et al 2020).…”
Section: Hints Toward a Therapymentioning
confidence: 99%